Development of Electronic Bonding Modules Using the Autocad Program for Students SMK Negeri 2 Merangin - Mizian, Zuhdi; Saputri, Sisca Meidina (PPSDP International Journal of Education, 2023)
This study aims to produce interactive multimedia products bonding bricks using the AutoCAD program for students of SMK Negeri 2 Merangin that are attractive, effective, and efficient. This interactive multimedia development procedure uses the Lee & Owens development model. The model development process consists of five stages of development, namely: (1) needs analysis, (2) design, (3) development, (4) implementation and (5) evaluation. The data collected in this study were obtained from material experts, media experts, small group trials of 3 people, and large group trials of 10 people. The results showed that: (1) The development of the brick bonding electronic module using the AutoCAD program for students at SMK Negeri 2 Merangin was assessed by the validator as in the good category. (2) aspects of the attractiveness of the developed multi-media learning are very good. (3) the use of interactive multimedia is effective on student learning outcomes. Based on the results of this research, the multimedia products developed are very interesting, effective, and efficient to use as a source of learning and can help students in learning. This multimedia product can also be used for independent learning or as a companion medium for teachers in the learning process.